(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2022)
Van Wyk-Grumbach Syndrome (VWGS) is presented by juvenile hypothyroidism, delayed bone age and isosexual precocious puberty. All of the features will be reversed with treatment of the underlying thyroid hormone deficiency. It has been described, a 3- year-old girl with Down Syndrome who presented with per vaginal bleeding. Physical examination showed typical morphologic features of Down Syndrome and hypothyroidism. Pubertal developments in tanner stages were: breast at stage II and pubic hair at stage I. Serum TSH level was very high. Serum FSH, LH and Estrogen level were also high for her age. On radiological examination her bone age was 2 years. Her pelvic sonogram revealed enlarged uterus with ovarian cysts. These findings confirmed the diagnosis of VWGS. Treatment with Levothyroxine, her vaginal bleeding did not recur and ovarian cyst size decreased after 4 weeks and disappeared after 2 months. In conclusion, thyroid hypo-function must be investigated in children who have precocious puberty with multicystic enlarged ovaries. JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 97-99